Interfaces entre psicopatolgia e neuropsicologia na infância e adolescência : funções executivas e aprendizagem no TDAH e no Transtorno Bipolar - Viapiana, Vanisa Fante (2021)
Psychopathology in childhood and adolescence is still less explored when compared to psychopathology in adults. However, it is increasingly common to request neuropsychological assessment in child psychiatric disturbance. From a neuropsychological point of view, executive functions (EF) have been considered transdiagnostic processes associated with psychopathology. In this perspective, Attention Deficit Hyperactivity Disorder (ADHD) is widely discussed, but there is still need for studies that refine the understanding of cognitive variability and school performance. On the other hand, Bipolar Disorder (BD) in children is often overlooked in the neuropsychological literature, possibly due to diagnostic difficulties in childhood and adolescence. Thus, the present doctoral thesis sought to investigate the interfaces between ADHD, BD, neuropsychological performance (with focus on executive functions) and school learning outcomes. To this end, three empirical studies were carried out. The studies included the neuropsychological assessment of children and adolescents (6 to 18 years old) with BD and / or ADHD, and in typical development. The participants in the clinical groups were referred by doctors, and they showed real demands for neuropsychological assessment. The first study aimed to verify the occurrence of dysfunctions and preserved cognitive abilities in children with BD and to investigate whether there are differences in neuropsychological performance according to specificities of the clinical diagnosis (BD subtypes and comorbidity with ADHD). In general, the results showed the high frequency of executive dysfunctions in children with BD, as well as the worsening of executive losses in Type 1 BD and in the presence of comorbidity with ADHD. In addition, the study presented preliminary results on the applicability of a complementary cognitive efficiency score (which assesses the relationship between speed and accuracy in solving cognitive tasks) to assess differences in executive functioning. The second study investigated the relationships between ADHD diagnosis and cognitive performance. From an analysis of hierarchical clusters, two school performance profiles were found, one with average school performance in reading, writing and arithmetic (A-SAP) and the other with reduced performance in the three basic school areas (L-SAP). Children with ADHD were distributed between the two clusters, but the L-SAP cluster was composed, mostly of children with the diagnosis. After conducting a factor analysis that resulted in 5 cognitive-executive factors, L-SAP was associated with more cognitive dysfunction than the diagnosis of ADHD, reinforcing the relationship between EF and school learning. The latest study found the existence of differences in executive processing, cognitive efficiency and school performance in children and adolescents with ADHD, BD, BD+ ADHD and in typical development. A factor analysis procedure found 4 cognitive-executive factors. The results show 1) wider range of difficulties in EF in the presence of BD + ADHD comorbidity; 2) the applicability of the efficiency score as a complementary score that enables the assessment of the cognitive overload required for the task, or even the verification of the impact of impulsivity on executive effectiveness; and 3) the association of child psychopathology with the risk of negative school learning outcomes. The clinical and school implications of executive variability associated with child psychopathology are discussed.